Intestinal Strictures Post-Necrotising Enterocolitis: Clinical Profile and Risk Factors - Phad, Nilkant; Trivedi, Amit; Todd, David; Lakkundi, Anil (Journal of Neonatal Surgery, 2014)
Background: Intestinal stricture is an important complication of necrotising enterocolitis (NEC). We aimed to describe clinical profile and identify the risk factors for post-NEC intestinal strictures. Method: A retrospective study of infants with NEC over 10 year period. Results: Of the 61 infants with NEC, 18 (29.5%) developed intestinal strictures. Leucocytosis and longer length of bowel resection during acute stage of NEC was associated with a later diagnosis of intestinal stricture. Infants with NEC who did not develop stricture had non-specific intestinal dilatation on abdominal x-ray during acute NEC. Intestinal strictures were diagnosed at a median interval of 34 days after NEC. Majority of strictures (67%) occurred in the colon. A significant proportion (77%) of infants with intestinal stricture had associated co-morbidities. No mortality occurred in infants with intestinal strictures. Conclusion: The incidence of post-NEC intestinal stricture is high but development of stricture is difficult to predict. Leucocytosis during NEC and length of bowel resected at surgery may be associated with development of post-NEC intestinal stricture. A substantial number of infants with post-NEC intestinal stricture fail to thrive, have co-morbidities and need prolonged hospitalisation.